(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Affandi R, Santosa Y, Kwatrina RT. 2025. Diversity of diurnal birds and their ecological role in Papua’s oil palm plantation landscape, Indonesia. Biodiversitas 26: 799-809. Oil palm plantations significantly impact biodiversity, particularly in Indonesia, where they play a crucial economic role. However, the ecological consequences remain underexplored in Papua, especially for avian communities. This study examines bird diversity and ecological roles within Papua’s oil palm agroecosystem. Observations were conducted in various land cover types in Kaureh Sub-district, Jayapura District, Papua, Indonesia, including oil palm blocks, High Conservation Value (HCV) areas, secondary forests, and shrubs. Using transect surveys, we recorded 46 bird species from 23 families, with the highest species richness in HCV areas. Bird communities contribute vital ecosystem services such as seed dispersal, pollination, and pest control. Granivorous and frugivorous species facilitate habitat regeneration, while insectivorous birds mitigate pest outbreaks, reducing the need for chemical pesticides. Raptors and carnivorous species regulate small mammal populations, enhancing ecological stability. Statistical analysis revealed significant correlations between bird abundance and environmental factors, including vegetation diversity and proximity to HCV areas. Despite their ecological importance, oil palm plantations exhibited lower species richness and evenness than natural habitats. Conservation strategies should integrate bird-friendly management practices, such as maintaining native vegetation, establishing ecological corridors, and minimizing chemical inputs. Enhancing biodiversity in oil palm landscapes can support agricultural productivity and environmental sustainability. This study underscores the need for further research and conservation efforts to balance economic gains with biodiversity preservation in Papua’s oil palm agroecosystems.